Vibration Monitoring System for Optimization of the Electrical Energy Production - Elmaati, Hassane; Benbouaza, Abdelkader; Elkihel, Bachir; Delaunois, Fabienne (Current Approaches in Engineering Research and Technology Vol. 3, 2024)
Generally, rotating machines produce vibration due to the dynamic forces of the machines, which include rolling elements and the structures that are connected to the machine. The vibrations are often responsible for the failure of the machine. This article presents the development of a vibration monitoring system based on the method of spectral analysis at a strategic facility, such as a feed pump in a thermal power plant, with the aim of optimizing the production of electrical energy. The chosen site for this study was the thermal power plant with three units, each of which was provided with two alimentary pumps (one in operation and the other on standby). Indeed, the maintenance policy practiced before at the pumps has demonstrated its failure after recording several outages in this facility, resulting in huge production losses over the past 10 years. This method is limited to the overall vibration measurements at different levels of feed pumps and the irregulars, then comparing these measurements with reference values constituting the signatures alert and danger of these pumps. Thus, this method does not allow to identification of possible causes of excessive vibration at different levels of the pumps. For cons, the new maintenance policy to establish the level of these pumps is a vibration monitoring to track the health of the system in operation and thereby detect any problems and trends in order to plan timely corrective actions. The expected profit from the implementation of this monitoring policy includes minimization of incident costs (repairs, downtimes) by early detection of abnormalities, minimization of maintenance costs and others.